Efektivitas Kebijakan Layanan BPJS Kesehatan Tanpa Kartu Cukup E-KTP di Kabupaten Karawang - Tatang Ruslih; Iwan Kurniawan Subagja; Azis Hakim (Jurnal Ekonomi Manajemen Sistem Informasi, 2026)
The BPJS Kesehatan cardless service using e-KTP in Karawang Regency is an innovation to accelerate healthcare access for JKN participants. This study examines the effectiveness of the policy implementation at the BPJS Kesehatan Karawang Branch Office, focusing on organizational culture, officer behavior, and digital public communication. A descriptive qualitative approach was employed, with data obtained from official documents, public performance reports, and official social media content of BPJS Kesehatan Karawang Branch for 2024-2025. The findings suggest that utilizing official social media as a public education channel enhances participants' understanding of the e-KTP service. The strengthening of BerAKHLAK values, particularly Service Orientation and Adaptiveness, serves as a key factor in ensuring consistent information delivery. However, inconsistencies across public communication channels and work culture resistance among some officers remain challenges. The study recommends strengthening transformational leadership, standardizing digital public communication, and integrating organizational culture evaluation into the SAKIP of BPJS Kesehatan Karawang Branch to enhance public service effectiveness.